"There wasn't any build up to it, it was just like, now you have to go over." Disengagement during the Child to Adult Community Mental Health Service Transition. Issue 4 (July 2023) - Cohen, Deborah Ann; Londoño, Tatiana; Klodnick, Vanessa Vorhies; Emerson, Kaleigh R.; Stevens, Laura
This study explored the personal, real-time experience of accessing adult mental health services after aging out of child mental health services. Mean age of the 19 participants at enrollment was 18. Eleven identified as women, five as men, and two as gender non-conforming. Over half of the sample identified as Hispanic or Latinx. This study employed a longitudinal, qualitative design with three interviews over 12-months (e.g., baseline, 6-months, 12-months), and monthly check-ins to prevent study attrition. Interviews explored previous and current mental health service experiences; the transition experience from child-to-adult services, and perceived service barriers and facilitators. Research team members used thematic coding to code each interview individually, focusing on identifying the disengagement timeline, experience, and related factors. Universally, participants saw a benefit in continuing mental health services, but almost all disengaged due to difficulty in navigating care and getting their needs met during the transition from child to adult services. This study provides a young adult perspective on the real gap between child and adult services within one community mental health agency. Improved transition practices and tailoring services to young adult development may prevent mental health disengagement during the transition from child to adult service systems.